1982
DOI: 10.2172/5361834
|View full text |Cite
|
Sign up to set email alerts
|

Disposal of liquid radioactive wastes through wells or shafts

Abstract: This report describes disposal of liquids and, in some cases, suitable solids and/or entrapped gases, through (1) well injection into deep permeable strata, bounded by impermeable layers, (2) grout injection into an impermeable host rock, forming fractures in which the waste solidifies, and (3) slurrying into excavated subsurface cavities. Radioactive materials are presently being disposed of worldwide using all three techniques. However, it would appear that if the techniques were verified as posing minimum h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Cement grouts monoliths will help support the overalso have a basic pH, which ensures head rock. This technique is somethe formation of hydroxides of very low times used in underground mining of solubility for most metal cations that ores (26).…”
Section: Selecting Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cement grouts monoliths will help support the overalso have a basic pH, which ensures head rock. This technique is somethe formation of hydroxides of very low times used in underground mining of solubility for most metal cations that ores (26).…”
Section: Selecting Componentsmentioning
confidence: 99%
“…Cement is a readily available, low-cost material that, with time, converts from a pumpable liquid state into a strong solid. As a direct consequence, the cost for underground disposal of wastecement-based grout mixtures may be only one-fifth of that for packaged waste disposal (26), while higher safety margins are provided.…”
mentioning
confidence: 99%
“…The water temperatures at the end of the crop furrows can be quite warm. In some instances, the release of aged acrolein-depleted water can produce fish kills and can release soluble and insoluble byproducts into other groundwater systems by direct means such as laterals back into flow canals, ponds, lakes, and estuaries or by seepage into underground aquifers. , Studies have shown that there is communication between oilfield waters and water tables. When used in oilfield waters, a water-soluble byproduct could be feasibly transferred from oil–water reservoirs to groundwater aquifers. Surface batch or subsurface slug treatments of acrolein in oilfield systems also produce high concentrations of acrolein at the injection point, and most systems are hot.…”
Section: Introductionmentioning
confidence: 99%
“…With cement-waste disposal, caverns can be spaced so that other caverns can be constructed between them after they are built and filled, since the cement monoliths will help support the overhead rock. This technique is sometimes used in underground mining of ores (26).…”
mentioning
confidence: 99%